IMPLEMENTASI TATA KELOLA PEMERINTAHAN YANG BAIK DALAM MEWUJUDKAN KUALITAS PELAYANAN PUBLIK (STUDI MULTI SITUS DI KELURAHAN SIDOMUKTI DAN KELURAHAN SEMAMPIR) - Agus Suprayoga; Sugeng Mulyono; Djuni Farhan (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
Good governance in the village or sub-district must be carried out in a structured and systematic manner so that it is not only accountable for all activities carried out but also can increase the competitiveness of the village. This means that with good management, the government can have clear directions and goals to achieve. Based on this, this research study aims to find out how to implement good governance in realizing the quality of public services in Sidomukti Village and Semampir Village, Kraksaan District. Qualitative research is a scientific research, which aims to understand a phenomenon in a natural social context by prioritizing the process of deep communication interaction between researchers and the phenomenon under study. Researchers took the research location with observations in Sidomukti Village and Semampir Village, Kraksaan District, Probolinggo Regency, in order to support the data needed in research related to the implementation of good governance in realizing the quality of public services. Sources of data obtained from the field where the research was carried out. To obtain this data, the interview method was used. This data was obtained from the results of the answers of related informants. The results of this study are as follows: (1) The implementation of governance in Sidomukti and Semampir villages has implemented good governance in serving administrative services, both population administration and government administration. (2) Obstacles in the implementation of governance are: HR problems (leadership commitment, quality and morality of human resources and the system as a determining factor for the performance of local government bureaucracy which is still not satisfactory and inadequate population administration facilities become obstacles in public services. (3 ) Solutions in resolving the obstacles to implementing internal bureaucratic reform are: Kelurahan cooperates with related agencies to increase resource capacity, access communication between kelurahan employees and the community, and optimize the role of organizations in Sidomukti and Semampir Villages.